THE NAJJAH STORE MARKETING COMMUNICATION STRATEGY TO IMPROVE PERSONAL BRANDING ON FACEBOOK - Rezeki Bintang; Abdul Rasyid (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: In the current virtual generation, there are many internet-based social media tools available, which are generally in the form of websites. This site can be used as a means of social networking interaction. One of the most popular social media in the world is Facebook. The business process with the media of information and communication technology and the Internet is known as e-trade, meaning that businesses that use digital space as a place for several companies to provide e-trade to display their business through the e-trade internet site, this encourages the creation of an electronic market called the e-trade market. . In increasing consumer buying interest and creating trust in the products provided in online stores or olshops, they usually use special strategies to achieve the olshop's goals. One of the strategies used is to increase personal branding. In the big Indonesian dictionary the word